Border disputes between the countries of Latin America (1825 – 1884) (Journal of the College of Education for Women, 2019)
The common history of Latin America countries may contribute significantly to determine the initial beginnings of these States since the current borders are a reflection and drawing of the borders of Antarctica according to the divisions determined by the behavior of the Portuguese and Spanish colonialism as well as what the Pope originally called for in order to divide property between Spain and Portugal. A later change took place especially after the independence in the first quarter of the 19th century for the majority of those States which is something that imposed special consideration in the analysis and description of each of these States. There are constants and variables in this case where all the States share constants, while the variables worked on their part to change certain attributes of certain States not affected by other parties. Border disputes between States is Latin America in the 19th century is one of the important topics in the history of this continent since it established the natural borders between these countries and on the basis of which some small countries were founded such as Uruguay in 1825 to be a borderline between Argentina and Brazil.